Needs assessment, training program and evaluation of Dhaka Bank Ltd (Islamic Banking Branch) - Kader, Sumaiya (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.